Dynamization: The Quantum Science of Homoeopathy (Advancements in Homeopathic Research, 2022)
Advancements in scientific techniques have enabled researchers to critically examine and scrutinize nonconventional therapies to either validate or reject them for routine clinical practice. The substantiation of the homeopathic system has been controversial since there is no standard drug dilution strength that can be subjected to clinical tests. Homeopaths usually claim to achieve curative effects by using homeopathic substances ranging in concentration from mother tinctures in crude forms to infinitesimal dilutions with a probability of almost zero active ingredients in them. The issue becomes further confused when different criteria are applied to drug dilution preparations that are inconsistent with any established scientific metric such as Avogadro’s number.
Keywords: Drug dynamization; homoeopathy; moleculer theory; water memory